Соматичні права людини з позицій юридичної антропології - Завальнюк, Володимир Васильович; Завальнюк, Владимир Васильевич; Zaval'njuk, Vladimir (My University, 2011)
Anthropological approach to the fourth generation of human rights is used. The need of referring somatic rights to the group of individual human rights is concluded. The system of somatic human rights in Ukrainian law is proposed.
Завальнюк В. В. Соматичні права людини з позицій юридичної антропології / В. В. Завальнюк // Наукові праці Національного університету «Одеська юридична академія». Т. 10 / голов. ред. С. В. Ківалов ; МОНмолодьспорт України, НУ "ОЮА". – Одеса : Юрид. л-ра, 2011. – C. 20-27.
Keywords: соматичні права; четверте покоління прав людини; юридична антропологія; персоноцентрична правова система; соматические права; четвертое поколение прав человека; юридическая антропология; персоноцентрическая правовая система; somatic rights; the fourth generation of human rights; legal anthropology; personotsentricheskaya legal system